HYPERURICEMIA AND ITS CORRELATES IN THE RUSSIAN POPULATION (RESULTS OF ESSE-RF EPIDEMIOLOGICAL STUDY) - S. A. Shalnova; A. D. Deev; G. V. Artamonov; D. V. Duplyakov; A. Yu. Efanov; Yu. V. Zhernakova; A. O. Konradi; R. A. Libis; G. A. Muromtseva; S. V. Nedogoda; E. V. Oschepkova; S. V. Romanchuk; et al. (Столичная издательская компания, 2015)
Aim. To study the prevalence of hyperuricemia in the Russian regions, depending on the climatic, geographical, socio-demographic characteristics and some cardiometabolic risk factors. Material and methods. Data from the ESSE-RF study from 10 regions of theRussian Federationare presented. All study participants were examined according to a uniform protocol. Measurements were standardized, biochemical tests were carried out in three Federal centers using the same methodology. The study was approved by independent Ethics committees, and all participants signed informed consent. Results. The prevalence of hyperuricemia was 16.8% (25.3% in men and 11.3% in women; p<0.0001). Hyperuricemia incidence increases with age, does not depend on education, significantly associates with place of residence, elevated blood pressure, obesity and abdominal obesity, alcohol consumption and diuretics taking. After adjustment for all factors included in the regression analysis, prevalence of hyperuricemia in the Ivanovo Region is 1.4 times higher than this in the reference region (Tyumen), while prevalence of hyperuricemia in the Samara Region and theRepublicofNorth Ossetia-Alaniais 30% and 40 % lower. Conclusion. Prevalence of hyperuricemia inRussiais defined; regions with the highest and lowest prevalence are identified. Associations of hyperuricemia with some social and demographic characteristics as well as cardiovascular risk factors are revealed.